CUTTING WEIGHT, PERCENTAGE OF CARCASS AND FAT ABDOMINAL CHICKEN BROILER fed WITH ADDITIONAL RED SWEET POTATOES POWDER (IPOMOEA BATATAS) - Leesi, Wa Ode Nurullah; Hafid, Harapin; Pagala, Muhammad Amrullah (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
This study aims to examine the use of red sweet potato flour on slaughter weight, percentage ofcarcass weight, and abdominal fat in broiler chickens fed with additional red sweet potato flour. Thisresearch was conducted in April to May 2018, housed in the Raman Farm enclosure in Puosu JayaVillage, Konda District, Konawe Selatan District. The material used in this study was 64 weeks oldbroiler chickens, with 64 feed ingredients used as the concentrate, corn, bean, sweet potato flour. Theequipment used is a scale, a colony cage made of wire-lined wood and measuring 4m x 2m, which isdivided into 16 plots and the size of each 1m x 0.5m, each story is equipped with a place to eat anddrink, 40-watt incandescent balloons and other equipment such as scales, ovens, sample grinders,basins, plastics, and gutters. This study was designed using a complete randomized design with fourtreatments and four replications, where four treatments consisted of P0 basic ration (Control), P1:basic ration containing 4% red sweet potato flour, P2: elemental percentage containing 6% red sweetpotato flour, and P3: basic ration contains 8% red sweet potato flour. The variables observed in thisstudy were cutting weight, carcass percentage, and abdominal fat of broiler chickens. The results ofthe analysis of variance showed that the administration of red sweet potato flour had no significanteffect (P> 0.05) on the percentage of carcasses and abdominal fat of broiler chickens. Broiler chickenaged five weeks. It was concluded that the provision of different red sweet potato flour in feed did notsignificantly affect slaughter weight, carcass weight, and abdominal fat percentage of broilerchickens. There is a tendency for broilers fed with red sweet potato flour to have heavier cut weights,a more significant portion of carcasses and an increase in the level of red yam, and a decrease inabdominal fat content and the addition of red yam levels in the feed.